2016
DOI: 10.3906/tar-1502-87
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long term soil management practices on the fertility andweed flora of an almond orchard

Abstract: IntroductionSoil management techniques can definitely influence soil quality, acting especially on soil organic matter content, biological complexity, structure, and water holding capacity (Kladivko, 2001). In the rain-fed orchards of the semiarid Mediterranean agrosystems, where soil conservation is one of the major agronomic challenges (Ramos et al., 2011), soil management is limited by the particular climate conditions, characterized by water deficits in the springsummer period.Therefore, agricultural pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
2
4
3
Order By: Relevance
“…Another study in a Spanish almond system also found that by comparison with CT, NT resulted in higher enzymatic activity for dehydrogenase (+37%), β-glucosidase (+93%) and phosphatase (+87%). However, in contrast with our latter findings, lower soil and leaf nutrient levels in NT than in CT, the studies by Ramos et al (2011) and Cucci et al (2016) report higher soil N content for NT than for CT. The relationship between NT and soil N content seems to be variable, as Martínez-Mena et al (2013) did not find differences between NT and CT in almond orchards, and Gómez et al (2009) reported a reduction in soil N content with NT in olive orchards.…”
Section: Nutrient Cyclingcontrasting
confidence: 99%
See 1 more Smart Citation
“…Another study in a Spanish almond system also found that by comparison with CT, NT resulted in higher enzymatic activity for dehydrogenase (+37%), β-glucosidase (+93%) and phosphatase (+87%). However, in contrast with our latter findings, lower soil and leaf nutrient levels in NT than in CT, the studies by Ramos et al (2011) and Cucci et al (2016) report higher soil N content for NT than for CT. The relationship between NT and soil N content seems to be variable, as Martínez-Mena et al (2013) did not find differences between NT and CT in almond orchards, and Gómez et al (2009) reported a reduction in soil N content with NT in olive orchards.…”
Section: Nutrient Cyclingcontrasting
confidence: 99%
“…Conventional agricultural management maximises the ecosystem service 'food provisioning', which may disrupt the balance with regulating, supporting and other provisioning ecosystem services (Kremen and Miles, 2012). For example, compared to agroecological management, conventional management in Mediterranean woody-crop systems resulted in 20-40% less understory vegetation cover (Cucci et al, 2016;Fracchiolla et al, 2015), 32-51% lower soil organic carbon content (Almagro et al, 2016;Ramos et al, 2011), 27-86% less efficient breakdown of organic phosphorus compounds in the soil (Hernández et al, 2005;Ramos et al, 2011), increased erosion and runoff, and reduced pest control and pollination services (Durán Zuazo et al, 2008;Eilers and Klein, 2009;Klein et al, 2012). In contrast, understory vegetation was associated with increased soil microbial activity (Ramos et al, 2011), less erosion and runoff (Durán Zuazo et al, 2006), and increased pollinator abundance (Saunders et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It includes the preparation of plant and animal products for people to use and their distribution to markets. Agriculture not only provides food and raw material but also employment opportunities to a very large proportion of the population (Sahin et al, 2002;Erturk et al, 2010;Cucci et al, 2016;Sorkheh and Khaleghi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that relatively lower values were obtained compared to the control. Cucci et al (2015) reported that the variations in available phosphorus and exchangeable potassium were negligible and not statistically different between the various treatments.…”
Section: Discussionmentioning
confidence: 93%